If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 120 + -1z = 8 Solving 120 + -1z = 8 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-120' to each side of the equation. 120 + -120 + -1z = 8 + -120 Combine like terms: 120 + -120 = 0 0 + -1z = 8 + -120 -1z = 8 + -120 Combine like terms: 8 + -120 = -112 -1z = -112 Divide each side by '-1'. z = 112 Simplifying z = 112
| 3x^4-27x^2-1200=0 | | 3(4g-7)=12+g | | 5n-150=4n+160 | | X^3+4x^2=10 | | x^5(5-5)4c= | | x^3+10x=24 | | -5k+1= | | 2(4x+1)+5(x+2)=-7 | | x*2+25=0 | | 106=-8-6a | | x^5(5-5)= | | 3f-9=60 | | 5v-2=7v+8 | | 4x-2y+z=2 | | 3(5x-7)=2(3x+5) | | 729=3x | | 2345-d=32 | | h^2-2h-63=0 | | -3c^2-6c+9=0 | | h^2+5h-20=-20 | | 9=a+13 | | x+(x*0.16)=300 | | 2y=9x+5 | | 35-5n= | | 4(x+2)=6(x-2)-10 | | h^2-12h+20=0 | | 13=20-9x | | 24x^2+73x+24=0 | | ln(x^2)=9-.5x^2 | | 4x-10+3x+4=180 | | -32x^2-36x-4=0 | | 3x-28=2x-12 |